The Acute Phase Proteins Reaction in Children Suffering from Pseudocroup - Beata Pucher; Magdalena Sobieska; Michal Grzegorowski; Jaroslaw Szydlowski (Mediators of Inflammation)
The aim of the study was to evaluate the inflammatory reaction in children with pseudocroup and compare it with other laryngological diseases according to the available literature data. The study group included 51 children hospitalized because of pseudocroup. The measurements of the acute phase proteins (APP), such as C-reactive protein (CRP), alpha-1-antitrypsin (AT), alpha-1-antichymotrypsin (ACT), alpha-1-acid glycoprotein (AGP), ceruloplasmin (Cp), transferrin (Tf), alpha-2-macroglobulin (A2M), and haptoglobin (Hp) were obtained at 3 time points. The glycosylation profiles of AGP, ACT, and Tf were completed. An increased AGP level was observed in girls. The AGP glycosylation revealed the advantage of the W0 variant over the W1 variant. W1 and W2 were decreased in boys. W3 emerged in boys. The Tf concentration and T4 variant were lower compared to the control group. The A2M level was lower after treatment. The Hp and AT levels were decreased a few weeks later. The ACT glycosylation revealed a decrease of the A4 variant in boys. In conclusion, the inflammatory reaction during pseudocroup was of low intensity. The APP glycosylation suggested a chronic process. In a follow-up investigation, no normalization of the parameters was noted, but signs of persistent inflammation were observed.